Excision of vulval neurofibroma - Gezer, Altay; Aslan, Berna; Erenel, Hakan; Çetin, Orkun; Vurallı Bakkaloğlu, Doğu; Dervişoğlu, Sergülen; İlvan, Şennur (Cerrahpaşa Medical Journal, 2013)
Neurofibromatosis type 1 and neurofibromatosis type 2 are inherited autosomal dominant disorders that have significant impact on the nervous system and predispose to tumour formation. Vulval neurofibroma is a rare cause of vulval lesions. Neurofibromas are characteristic of neurofibromatosis type 1. A 23 year old patient admitted with the complaint of 12x15 cm mass at the left mabia majora. On examination one cafe au lait patch were seen on the left leg. Vulval mass was mobil, soft and painless. Local excision and primary closure were performed. The histopathology of the mass was pigmented neurofibroma without evidence of malignant transformation. Vulval neurofibroma is rare entity and it needs to be differentiated from other rare vulval lesions. Local excision is adequate treatment to prevent malignant trasformation and it resolve cosmetic issues.